23. RELIABILITY AND VALIDITY OF THE KCCQ-12 FOR ASSESSING THE QUALITY OF LIFE AMONG PATIENTS WITH CHRONIC HEART FAILURE (Vietnam Journal of Community Medicine, 2023)
Objective: The study was conducted to evaluate the internal consistency and validity of the Vietnamese version of the Kansas City Cardiomyopathy Questionaire (KCCQ-12). Subject and method: A cross-sectional study on 182 in patient older adults with chronic heart failure at the National Geriatric Hospital. For reliability, internal consistency was assessed using Cronbach’s α, and test–retest reliability (Intraclass correlation coefficient -ICC ) was assessed. The associations of baseline KCCQ scores with New York Heart Association (NYHA) class and the EuroQol five-dimension, five-level (EQ-5D-5L) scores were analyzed for construct validity. Results: The internal consistency of the KCCQ-12 questionnaire was high, with a Cronbach’s Alpha score of 0.89 for all of the KCCQ-12 scale and 0.75-0.88 for subgroups of the scale. The test– retest analysis demonstrated good reproducibility with an intraclass correlation coefficient > 0.7. Convergent validity showed the correlation between KCCQ-12 with EQ-5D-5L and NYHA. Conclusion: The Vietnamese version of KCCQ-12 has high internal consistency and shows high validity in measuring the health status of patients with chronic heart failure.
Keywords: Quality of life, heart failure, KCCQ-12.